Assessing Vietnam’s Maritime Diplomacy to China and Searching for Some Possible Responses of Vietnam in the South China Sea (Biển Đông) - Anthony Setiawan Hartono; Nguyen Thao Phuong; Anak Agung Banyu Perwita, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
China’s growing assertiveness in the South China Sea (SCS) has long been recognized and considered as a big threat to regional peace and stability. Such perversity has triggered territorial and overlapping claim disputes among countries in the region, including Vietnam, a neck-to-neck neighbor with China. Despite all possible efforts, the stagnation of Vietnam’s resolution to deal with this matter in recent years has been problematic which raises the authors’ concern about the potential effective response that Hanoi might take in resolving the complexity of the dispute. Firstly, it is important to understand Vietnam’s interests in the SCS and its long-term stance in the area. Secondly, to explain the modest action of Vietnam towards China in the SCS, it is key to realize its undeniable economic reliance on this powerful neighbor. Meanwhile, China has continuously posed its massive power over Vietnam’s Sea territory which threatened its security. Hence, the readers can understand the intricate relationship that Vietnam is tied up in. Besides this, the authors also analyze the current maritime diplomacy that is pursued by Vietnam along with its effectiveness which becomes the foundation for suggesting the future strategies of Vietnam based on internal balancing and multidirectionalism in its foreign policy.Received 7th August 2020; Revised 2nd June 2021; Accepted 20th August 2021